THE EFFECT OF SERVICE QUALITY OF CUSTOMER SERVICE TO CUSTOMER SATISFACTION IN ASIAN CENTRAL BANK OF TANJUNG PRIOK BRANCH OF NORTH JAKARTA - Suryani, Dessy; Kurniawan, Aris; Siregar, Otto (STIE Kusuma Negara, 2019)
This research uses a quantitative approach, and the analysis used is simple linear regression. The sampling technique used was Purposive Sampling by selecting respondents with certain considerations, namely: The number of respondents taken in this study were 100 respondents of Bank BCA customers in Tanjung Priok Jakarta Branch. Based on the results of this study, it proves that an R value of R = 0.786 means that there is a positive and strong relationship between Customer Service Services and BCA Customer Satisfaction. This gives an indication that service quality affects Customer Satisfaction Based on the calculation of the Determination Coefficient (KD) the results obtained 61.8% which shows that the influence of service quality on customer satisfaction and the rest 38.2% which is influenced by other factors. Based on the calculation of a simple regression equation the equation Y = 18.532 + 0.560X.